حالت جنگ میں انسانی حقوق سے متعلق السیر الکبیر اور جینوا کنونشن کا تحقیقی و تقابلی جائزہ: Comparative and Analytical Study of Al-sair-ul-Kabir and Geneva Convention about Human Rights in War (Khairulummah, 2024)
War is a tragic and painful situation that every intelligent person wants to avoid or prevent, but in practice it is impossible. As Muslims, we also believe that this life is a test, we can be an ideal and role model for those who want to avoid war in order to live their lives in the best way. The struggle between good and evil will always continue. However, efforts can be made until the end of war, but the presence of war cannot be ignored. In this regard, if a war breaks out and combatants are injured, need to be transferred to a peaceful place or are affected in any way by the war and are no longer part of the war, it is morally necessary to protect them and provide humanitarian assistance to the victims.It serves humanity as a neutral organization founded in 1860. The name of this organization is the International Committee of the Red Cross (ICRC). After much work and deliberation, this organization has developed four treaties and two protocols that help countries at war remain neutral in war or other forms of violence۔In contrast, about 800 years ago, Imam Muhammad bin Hasan Al-Shaybani wrote a long but comprehensive book on the state of peace and war, "Al-Sair- Al-Kabir", and took the credit for preserving these laws in the form of a book before his death. This article provides a detailed explanation of the fundamental principles and laws governing human rights in war, as outlined in both texts.Keywords: Al-Qur’an, Geneva Convention, Al-sair-ul-Kabir, state of war, Compassionate, Patients, Ceasefire, Combatants